Advances in Root Vegetables Research - Kaushik, Prashant (IntechOpen, 2023)
Root vegetables are the sections of underground plants that are harvested and consumed by humans for their nutritional value. They are found in a wide variety of plant species. Even though botany draws a distinction between real roots and non-roots, the term "root vegetable" refers to both kinds in the context of agriculture and cuisine, despite botany classifying genuine roots as separate from non-roots. Root vegetables are often storage organs that store energy in the form of carbohydrates. This book explores recent developments in root vegetable research against the background of current and impending environmental change.